2014
DOI: 10.7314/apjcp.2014.15.16.6919
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Nuclear Morphometry in Effusion Cytology

Abstract: Background: The cytological analysis of serous effusions is a common investigation and yields important diagnostic information. However, the distinction of reactive mesothelial cells from malignant cells can sometimes be difficult for the cytopathologist. Hence cost-effective ancillary methods are essential to enhance the accuracy of cytological diagnosis. The aim of this study was to examine the utility of nuclear morphometry in differentiating reactive mesothelial cells from malignant cells in effusion smear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(24 reference statements)
2
6
0
Order By: Relevance
“…Values de ned by the ROC curve related to AR are results not used in other studies. Sensitivity and speci city values for nuclear perimeter in our study are similar to the values found by Ambroise et al [23] who showed that a cut-off level of 33.2 µm for nuclear perimeter could differentiate malignant and benign pleural effusions. However, despite the computer analysis by ImageJ following a similar methodology, they used analyses applied to effusion cytology, in addition to evaluating for each case only ten representative nuclei from ten different elds.…”
Section: Discussionsupporting
confidence: 90%
“…Values de ned by the ROC curve related to AR are results not used in other studies. Sensitivity and speci city values for nuclear perimeter in our study are similar to the values found by Ambroise et al [23] who showed that a cut-off level of 33.2 µm for nuclear perimeter could differentiate malignant and benign pleural effusions. However, despite the computer analysis by ImageJ following a similar methodology, they used analyses applied to effusion cytology, in addition to evaluating for each case only ten representative nuclei from ten different elds.…”
Section: Discussionsupporting
confidence: 90%
“…The procedure of finding the extreme PEs belonging to the sides of the quadrilateral is executed in 8 successive sub steps, that allow to identify the PEs ∈ {E, F, G, H, I, J, K, L} of the contour component. In each sub step, we applied the Min/Max algorithm [18] to the values of the abscissa and ordinates relating to the quadrilateral. The set of PEs belonging to this sub group are determined as follow: 1.…”
Section: (Iii)mentioning
confidence: 99%
“…3. All the PE j of group G execute the algorithm Max [18] to identify the two PEs which has the maximum distance and represent the extreme points of the object, where Dmax = Max {d1, d2, d3, d4, d5, d6, d7, d8, d9, d10, d11, d12, d13, d14, d15, d16}). The two PEs {PE n , PE m } of the group G, refer to the two points that defines the maximum diameter, thus represent the two extreme points of the component.…”
Section: (Iii)mentioning
confidence: 99%
See 2 more Smart Citations